Applying High-Temperature SuperconducTechnologies into Power Systems (The International Journal of Engineering & Information Technology (IJEIT), 2024)
implementing of distribution and transmission power systems for urban areas and for future renewableenergy to meet future demand is a challenging task whenconventional cables and transformers are considered.Therefore, there are several methods, that have applied inconational power systems to reduce power losses, voltage regulator issues , capital cost of whole system and increasingpower delivering in urban areas and from offshore farms,such as carefully sited and operated distributed generation(DG) and distributed control techniques. However, thesetechniques may raise others challenges in networks such as stability, voltage regulators issues and increasing capital costof networks. Since High Temperature Superconductor(HTS) cables exhibit zero resistance when cooled to theboiling point of liquid nitrogen (77Keliven), they have thepotential to be used to address these issues in distribution and transmission networks. Consequently, this paperreviews super-conductor power systems: the workpreviously achieved in the DC and AC superconductorpower systems and describes the materials and methodswhich they used. In addition, it shows how the superconductor technologies can address these issues whenthey are used for distribution and transmission powe r systems.